Factors Influencing General Dermatologists When Referring Patients With Head and Neck Melanoma for Mohs Micrographic Surgery: A Nationwide Cross-Sectional Survey. Issue 5 (22nd May 2023) - Neill, Brett C.; Siscos, Spyros M.; Bar, Anna A.; Seger, Edward W.; Latour, Emile; Tolkachjov, Stanislav N.
Abstract : BACKGROUND: Mohs micrographic surgery (MMS) for cutaneous melanoma has demonstrated higher cure rates, lower local recurrence rates, and improved survival compared with wide local excision (WLE). However, factors affecting referrals by general dermatologists for MMS of head and neck melanoma (HNM) are unknown. OBJECTIVE: To elucidate referral factors and treatment perspectives of general dermatologists regarding MMS for melanoma in situ (MIS)/lentigo maligna (LM) and early-stage melanoma on the head and neck. MATERIALS AND METHODS: A cross-sectional analysis was performed using survey responses of general dermatologists with membership in the American Academy of Dermatology. RESULTS: A total of 231 and 132 of the 402 responding general dermatologists routinely referred melanoma in situ MIS/LM and early invasive melanoma for MMS, respectively. Lack of local access to a Mohs surgeon was the most common deterring reason for MIS/LM referral to MMS, whereas the preference for WLE was the most common deterring reason for early invasive melanoma. CONCLUSION: Lack of local access to a Mohs surgeon treating HNM with MMS is the primary barrier in referrals to Mohs surgeons for MIS and LM. Among general dermatologists, WLE is preferred for early invasive HNM.